Revisiting the Minority Threat Perspective: Examining the Main and Interactive Effects of Segregation on Sentencing Severity. (7th June 2022) - Beckman, Laura; Wang, Xia
Abstract: Drawing on the minority threat perspective, this study assesses the main and interactive effects of racial/ethnic segregation on the incarceration and sentence length decisions. Using the State Court Processing Statistics in combination with other data, we employ multilevel models to examine (1) whether racial/ethnic segregation affects sentencing severity, (2) whether racial/ethnic segregation moderates the effects of racial/ethnic composition, and (3) whether racial/ethnic segregation reduces racial/ethnic disparity in punitive sentencing. Both racial and ethnic segregation displayed mitigating effects on punishment severity. In particular, racial segregation reduced the effect of racial composition on probabilities of receiving a prison term, and ethnic segregation reduced the effect of ethnic composition on probabilities of receiving a jail sentence. Our results suggest that the minority threat perspective and its theoretical accounts of segregation can be partially applied to sentencing outcomes in state courts.